Handmaids to the Doctor: Tracing the Subordination of Midwifery to Obstetrics in the 20th Century - Ali Al- Jubouri; Daniyar Satybaldy; Azamat Nazarov (Yayasan Adra Karima Hubbi, 2026)
Background. The twentieth century marked a fundamental transformation in childbirth practices, driven by the rise of obstetrics and the gradual subordination of midwifery within institutional healthcare systems. This shift redefined maternal care through clinical authority, technological intervention, and standardized protocols, while simultaneously reshaping professional hierarchies and gendered roles in medicine. Purpose. This study aimed to critically examine how midwifery was repositioned from an autonomous, community-based practice into a subordinate role under the dominance of obstetrics within modern healthcare institutions. Method. A qualitative historical research design was employed, integrating archival analysis, policy documents, and scholarly literature. The data were analyzed using thematic coding informed by feminist theory and the sociology-of-professions framework to explore shifts in power, knowledge, and professional identity. Results. The findings indicate that the subordination of midwifery was influenced not only by clinical advancements but also by regulatory mechanisms, institutional expansion, and epistemological hierarchies privileging biomedical knowledge over experiential practice. Evidence further shows that this transformation reshaped both professional identities and the nature of childbirth, shifting it from relational, woman-centered care toward standardized medical control. Conclusion. The study concludes that the rise of obstetrics represents a complex reconfiguration of power and knowledge rather than a purely linear progression of medical improvement. These findings provide important insights for contemporary discussions on maternal care, interprofessional collaboration, and the development of more patient-centered healthcare approaches.